Wound-dependent infection by Nigrospora oryzae causes sugarcane leaf spot: pathogen characterization and fungicide sensitivity - Yusuf Abubakar, Ahmad; Chen, Shujie; Lu, Qianqi; Abdullaziz, Sheidu; Ibrahim, Muhammed Mustapha; Zhang, Hua; Chen, Pinghua (Frontiers in Plant Science, 2026)
IntroductionNigrospora oryzae is increasingly detected in sugarcane fields, but its infection biology and effective chemical control options remain unclear.MethodsWe isolated the causal fungus from symptomatic sugarcane leaves and identified it using morphology and ITS phylogeny. Pathogenicity was tested on cultivar ROC22 using wounded and unwounded inoculations (mycelial plugs and spore suspensions). We assessed fungal growth across temperatures and pH, quantified host chlorophyll and defense-related responses (POD, SOD, PAL, and MDA), and evaluated sensitivity to commonly used fungicides using growth-inhibition assays.ResultsThe isolate (MF1) clustered with N. oryzae and caused lesions only on mechanically wounded leaves. Infection reduced chlorophyll content and increased POD, SOD, PAL activities and MDA accumulation. Optimal growth occurred around 25–30°C and near neutral pH. Among tested fungicides, pyraclostrobin + metiram and difenoconazole showed the strongest inhibition (lowest EC50), whereas several others were weak or ineffective.DiscussionThese results indicate N. oryzae acts as a wound-dependent opportunistic pathogen of sugarcane. The sensitivity profile provides baseline guidance for integrated management and resistance-aware fungicide selection.